ATTENTION TO DIVERSITY IN STUDENTS WITH SPINA BIFIDA IN THE AREA OF PHYSICAL EDUCATION: APPROXIMATION TO THE PROBLEM AND STRATEGIES TO DEVELOP IN THE REGULAR CLASSROOM. - López-Bastías, José Luis; Moreno-Rodríguez, Ricardo; Camarena, Inmaculada Garrote (IJRDO- Journal of Educational Research, 2017)
Students with a disability due to neural tube defect or spina bifida are often found in the ordinary classroom. The implications derived from its symptomology can produce a difficulty to achieve the objectives set by the teacher in the area of Physical Education. Taking into account the concept of disability advocated by the International Classification of Functioning, Disability and Health (CIF) and highlighting the difficulties encountered by teachers in their daily practice, the present article proposes a series of strategies and guidelines that facilitate daily task to the Physical Education teacher.